2020
DOI: 10.1111/his.14101
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus‐associated large B‐cell lymphoma transformation in marginal zone B‐cell lymphoma: a series of four cases

Abstract: AimsTo present four examples of clonally related Epstein–Barr virus (EBV)‐associated large‐cell transformation of marginal zone lymphoma (MZL) (of nodal, extranodal and splenic types), occurring 120, 11 and 5 months after the initial diagnosis in three instances, and concurrently in one case; and to discuss several interesting features of EBV infection.Methods and resultsSomatic mutations were detected by use of a customised panel for next‐generation sequencing and polymerase chain reaction studies of IgH in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This may be related to the fact that EBV does not infect tumor cells or the time of infection. According to Camacho Casta ñ EDA FI ( 8 ), one case of intranodal MZL was completely resolved after six cycles of chemotherapy. Lymph node biopsy showed scattered EBV-positive cells; 10 years later, the condition transformed into EBV-positive DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the fact that EBV does not infect tumor cells or the time of infection. According to Camacho Casta ñ EDA FI ( 8 ), one case of intranodal MZL was completely resolved after six cycles of chemotherapy. Lymph node biopsy showed scattered EBV-positive cells; 10 years later, the condition transformed into EBV-positive DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…EBV infection is associated with disease progression, and patients with EBV-positive lymphoma, diffuse large B-cell lymphoma, have a poor prognosis ( 4 ). Recent studies have found that some mature small B-cell lymphomas, such as follicular lymphoma (FL) and marginal zone lymphoma (MZL), are associated with EBV infection ( 5 8 ). Most of these cases are linked to aging, immunodeficiency, immunosuppression, and transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Primary gastric and thyroid DLBCLs often arise from antecedent EMZL through transformation, and almost all cases are EBV-negative. This suggests that most cases of EBV-positive DLBCL associated with chronic inflammation may not be related to EMZL and there may be a significant difference in oncogenesis between these two types of lymphoma, although some reports suggest that EBV infection might induce transformation from EMZL to DLBCL [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth notifying that recent data correlate EBV infection and large B cell lymphoma transformation in marginal zone B cell lymphoma. 126 Earlier report suggested that EBV may contribute to the pathogenesis of a small proportion of high-grade MALT lymphoma. 127 Analysis of molecular mechanisms of MZB cell transformation pointed the deregulation of NF-kB as one of the major players for MALT lymphomagenesis.…”
Section: Malt Lymphomamentioning
confidence: 99%